PENGARUH ON THE JOB TRAINING DAN KEMAMPUAN TRAINEE DI HOTEL SHANGRI-LA JAKARTA TERHADAP KESIAPAN KERJA - Nurmansyah, Farhan; Putri, Liza Amalia; Dwilanisusantya, Carissa (LPPM Politeknik Pajajaran ICB Bandung, 2023)
This study aims to analyze the influence of On the Job Training (OJT) and trainee competence on the job readiness of students participating in a training program at the Shangri-La Hotel Jakarta. Using an associative quantitative approach, 55 respondents were selected through purposive sampling. The research instrument was a Likert-scale questionnaire, and the data were analyzed using multiple linear regression with the assistance of SPSS 25. The results show that, simultaneously, OJT and trainee competence have a significant effect on job readiness. However, individually, only trainee competence has a significant effect, while OJT does not. This suggests that job readiness is more strongly influenced by the trainees' internal factors than by the technical aspects of the OJT program implementation itself.